2003
DOI: 10.1124/dmd.31.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Cytochrome P450 2B6 Allelic Variants

Abstract: ABSTRACT:Cytochrome P450 (P450) 2B6 is a hepatic enzyme of potential importance for the metabolism of clinically used drugs and environmental or abused toxicants. Genetic polymorphisms of CYP2B6 (CYP2B6*2, CYP2B6*3, CYP2B6*4, CYP2B6*5, CYP2B6*6 and CYP2B6*7; wild-type, CYP2B6*1) were found previously in white and Japanese populations. In the present study, the goal was to investigate the effects of amino acid substitutions on CYP2B6 function. Wild-type (CYP2B6.1) and all of the known variants of CYP2B6 (CYP2B6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
89
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 28 publications
5
89
3
2
Order By: Relevance
“…CYP2B6 variants have been associated with both decreased (Lang et al, 2001), (Jinno et al, 2003) and unchanged (Xie et al, 2003) protein expression compared with the wild-type gene. Increased specific activity associated with the variants has also been observed (Lang et al, 2001;Jinno et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2B6 variants have been associated with both decreased (Lang et al, 2001), (Jinno et al, 2003) and unchanged (Xie et al, 2003) protein expression compared with the wild-type gene. Increased specific activity associated with the variants has also been observed (Lang et al, 2001;Jinno et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…CYP2B6 variants have been associated with both decreased (Lang et al, 2001), (Jinno et al, 2003) and unchanged (Xie et al, 2003) protein expression compared with the wild-type gene. Increased specific activity associated with the variants has also been observed (Lang et al, 2001;Jinno et al, 2003). Similarly, though there are reports that CYP2B6 variants confer differences in the pharmacokinetics of cyclophosphamide (Xie et al, 2006), other studies have failed to show a statistically significant impact (Timm et al, 2005;Nakajima et al, 2007;Ekhart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that protein levels of variant CYP2B6 were less than that of wild-type CYP2B6 [21,33]. The activity of the CYP2B6 variants A785G and G516T was significantly higher than that of wild-type CYP2B6 [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Five of these polymorphisms cause amino acid substitutions in exons 1, 4, 5 and 9. Polymorphisms in the CYP2B6 gene have been shown to result in altered protein expression and activity [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation